TIME-CORRELATION OF LATE PERMIAN STRATIGRAPHIC SEQUENCES - Shang Q.; Cao C.; Jin Y. (My University, 2004)
The Upper Permian recorded the greatest mass extinction and the most dramatic environmental changes in geologic history. Understanding the process of these events has long been handicapped by the uncertainty of their synchronity of Late Permian sequences in major depositional regions. With the Lopingian Series as the global standard for the Upper Permian and a set of bio-, magneto- and sequence stratigraphic tie points, a global correlation of Lopingian rocks at stage-level is tentatively suggested.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская